Mechanism of improving oxygen transport resistance of polytetrafluoroethylene in catalyst layer for polymer electrolyte fuel cells. (12th April 2018) - Wan, Zhaohui; Liu, Sufen; Zhong, Qing; Jin, Aiping; Pan, Mu
Abstract: Oxygen transport resistance of catalyst layer (CL) has significant impact on the performance for polymer electrolyte fuel cells (PEFCs). Nano-Polytetrafluoroethylene (PTFE) particles are added into CL to improve the oxygen transport resistance. The CV curves indicate that PTFE do not reduce the utilization of Pt. The IV polarization curves suggest that the performance incorporated PTFE in CL gradually improve at high current densities and the output is 0.57 V at 1.8 A cm −2, 70 mV higher than that without PTFE. The water contact angle for CL with 20 wt% PTFE shows that continuous hydrophobic network may not be formed at 150 °C heat treatment temperature. The total transport resistance of CL with PTFE decreases about 2.5% at 70 °C and 250 kPa, mainly caused by the reduction of pressure-independent resistance ( R other ). In the R other reduction, the Knudsen diffusion resistance reduction in CL account for 74%. The pore size distributions reveal that the porosity increases 29% and the proportion of pores at around 100 nm increases for primary pores in CL with PTFE. This finding indicates that not the hydrophobicity of PTFE but the porous structure conducive to Knudsen diffusion for CL plays the predominant role in improving the performance. Highlights: Nano-PTFE were added into catalyst layer to improve the oxygen transport. The oxygen transport mechanism was analyzed by limiting current method. Pore size distributions were characterized to clarity the structure change.